Evaluation of methods for determining furrow infiltration characteristics - Rezende, Fátima da Conceição; Scaloppi, Edmar José (Pesquisa Agropecuaria Brasileira, 2014)
Furrow infiltration characteristics were evaluated by four methods based on the volume balance equation and the widely used inflow-outflow method. The methods were evaluated by performing a balance of volume using the calculated infiltration equations obtained by each method, and comparing the results to that determined by the infiltration test data. The results obtained revealed little differences among the methods based on the rate of advance data. The inflow-outflow method overestimated the infiltrated volume of water by 24% of that determined from test data.